2019
DOI: 10.3390/ani9060357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of In Ovo Injection of L-Arginine in Different Chicken Embryonic Development Stages on Post-Hatchability, Immune Response, and Myo-D and Myogenin Proteins

Abstract: The aim of this study was to evaluate the effect of in ovo injection with different ratios of L-arginine (L-Arg) into Ross broiler eggs at three different embryonic developmental stages (eighth day (d), 14th day, and 18th day) on the survival, hatchability, and body weight (BW) of one-day-old hatched chicks. Additionally, we have analyzed the levels of serum glutamate oxaloacetate transaminase (SGOT) and serum glutamate pyruvate transaminase (SGPT), the protein expression of heat shock proteins (HSPs), and we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
3
14
0
3
Order By: Relevance
“…Thus, increasing the concentration of Ag NPs could increase levels of SGOT and SGPT in the blood which can lead to liver function damage. In fact, free radicals from Ag NPs can attack hepatocytes and release stored SGOT and SGPT to re-enter the blood serum [37]. Injection of Ag NPs into chicken embryo did not result in any negative changes in SGOT or SGPT levels, in agreement with previous results from experiments carried out in ovo [38].…”
Section: Biochemical Indices (Sgot and Sgpt)supporting
confidence: 90%
“…Thus, increasing the concentration of Ag NPs could increase levels of SGOT and SGPT in the blood which can lead to liver function damage. In fact, free radicals from Ag NPs can attack hepatocytes and release stored SGOT and SGPT to re-enter the blood serum [37]. Injection of Ag NPs into chicken embryo did not result in any negative changes in SGOT or SGPT levels, in agreement with previous results from experiments carried out in ovo [38].…”
Section: Biochemical Indices (Sgot and Sgpt)supporting
confidence: 90%
“…In fact, free radicals from Ag NPs can attack hepatocytes and release stored SGOT and SGPT to re-enter the blood serum [27]. Injection of Ag NPs into chicken embryo did not result in any negative changes in SGOT or SGPT levels, in agreement with previous results from experiments carried out in ovo [8]. Some studies have reported that the size, superficial coating effect, concentration of particles, surface charge, Zeta potential, composition and crystal form of the Ag NPs influence toxicity in embryos [28].…”
Section: Biochemical Indices (Sgot and Sgpt)supporting
confidence: 90%
“…L-Arginine (L-Arg) is classified as an essential amino acid and it has been reported that in ovo administration of L-Arg in the embryonic phase could increase the growth rate and muscle mass for the reason that L-Arg can stimulate the release of growth hormone [6,7]. L-Arg (100 µg/µL/egg) injection at 14th day of chicken embryo increases chick body weight, hatch rate, muscle growth-related proteins and stimulates the immune response (IgM) [8].…”
Section: Introductionmentioning
confidence: 99%
“…The increased plasma level of cytokines observed in our study in turkeys is not indicative of immunosuppression, as postulated in our previous work ( Jankowski et al., 2020 ), but of mobilization of the immune system due to the reduced content of Arg relative to Lys in the cell. This is supported by the results of a study by Subramaniyan et al. (2019) , which demonstrated that Arg administered in ovo does not intensify but weakens inflammatory reactions, inhibiting the production of inflammatory mediators such as pro-inflammatory cytokines and C-reactive protein in chicken serum.…”
Section: Discussionmentioning
confidence: 55%